2014
DOI: 10.1186/1880-5981-66-103
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of the diurnal tides from eCMAM30 (1979 to 2010) and its comparison with SABER

Abstract: The extended Canadian Middle Atmosphere Model (eCMAM) was recently run in a nudged mode using reanalysis data from the ground to 1 hPa for the period of January 1979 to June 2010 (hence the name eCMAM30). In this paper, eCMAM30 temperature is used to examine the background mean temperature, the spectrum of the diurnal tides, and the climatology of the migrating diurnal tide Dw1 and three nonmigrating diurnal tides De3, Dw2, and Ds0 in the stratosphere, mesosphere, and lower thermosphere. The model results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 110 publications
8
75
0
Order By: Relevance
“…The appearance of the diurnal wave component in a particular altitude range is frequently related to a trapped mode of the tide, which cannot propagate upward. Such a local maximum of the diurnal tide has also been reported by, for example, Forbes and Wu (2006) and Gan et al (2014). However, results on the temporal variability are generally rare.…”
Section: Discussionsupporting
confidence: 52%
“…The appearance of the diurnal wave component in a particular altitude range is frequently related to a trapped mode of the tide, which cannot propagate upward. Such a local maximum of the diurnal tide has also been reported by, for example, Forbes and Wu (2006) and Gan et al (2014). However, results on the temporal variability are generally rare.…”
Section: Discussionsupporting
confidence: 52%
“…Nevertheless, we cannot exclude the possibility of tidal aliasing which could underestimate the semi-annual oscillation influence in lidar observations (Gan et al, 2012(Gan et al, , 2014Xu et al, 2007). Leblanc and Hauchecorne (1997) reported that some tidal residuals can affect the altitude and amplitude of some temperature inversions.…”
Section: Influence Of the Semi-annual Oscillationsmentioning
confidence: 99%
“…Due to the line of sight of SABER and the yaw maneuver of the TIMED satellite, the latitude coverage of SABER data is from 53 • latitude in one hemisphere to 83 • in the other. In the past decade, SABER temperature has been widely employed for the study of typical thermal structure (Gan et al, 2012) and wave dynamics (Huang et al, 2013;Gan et al, 2014). In the current work, the latest version of temperature data, 2.0, is utilized to identify the 6.5-day wave in temperature.…”
Section: Saber Temperature Datamentioning
confidence: 99%